2018
DOI: 10.1007/s10482-018-1073-1
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between carbon, nitrogen and phosphate utilization in the control of secondary metabolite production in Streptomyces

Abstract: Streptomyces species are a wide and diverse source of many therapeutic agents (antimicrobials, antineoplastic and antioxidants, to name a few) and represent an important source of compounds with potential applications in medicine. The effect of nitrogen, phosphate and carbon on the production of secondary metabolites has long been observed, but it was not until recently that the molecular mechanisms on which these effects rely were ascertained. In addition to the specific macronutrient regulatory mechanisms, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 115 publications
1
29
0
Order By: Relevance
“…However, A-factor seems to be essential in the induction of antibiotics and extracellular protease production, regardless of medium composition. Rich medium supports the production of more antibiotics that is in good agreement with the fact that secondary metabolites require nitrogen compound precursors [Romero-Rodríguez et al, 2018]. On the contrary, elevated extracellular protease production was observed during nutrient limitation.…”
Section: Discussionsupporting
confidence: 74%
“…However, A-factor seems to be essential in the induction of antibiotics and extracellular protease production, regardless of medium composition. Rich medium supports the production of more antibiotics that is in good agreement with the fact that secondary metabolites require nitrogen compound precursors [Romero-Rodríguez et al, 2018]. On the contrary, elevated extracellular protease production was observed during nutrient limitation.…”
Section: Discussionsupporting
confidence: 74%
“…Our study revealed the nature of the metabolic features underlying the drastically different abilities of SL and SC to produce antibiotics. We believe that these differences are likely to be due, at least in part, to the weaker expression of PhoR/PhoP in SC compared to SL leading to the relief of the indirect negative impact that PhoR/ PhoP exerts on antibiotic production 75,98 . However, since the causes of the low expression of PhoR/PhoP in SC remain to be clarified further investigation would be needed to confirm this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly recognized that antibiotic production is stringently regulated by pyramidal transcriptional regulatory cascades in Streptomyces. Recent years, there were several reviews on the regulatory networks of Streptomyces (Romero- Rodriguez et al, 2018;van der Heul et al, 2018;Palazzotto et al, 2019). So here we won't go into detail of the regulatory networks involved in antibiotic production.…”
Section: The Regulatory Cascades Of Antibiotic Production In Streptommentioning
confidence: 99%
“…It has been reported that GlnR and PhoR-PhoP was involved in the type of regulation depending on the carbon, nitrogen, and phosphate supply. For the similarity of binding sites, PhoP and GlnR showed competitive binding to target genes in some cases (Romero- Rodriguez et al, 2018). In Saccharopolyspora erythraea, the GlnR regulon is not only involved in nitrogen metabolism, but it also appears to control ABC-type transporters for uptake of carbon sources (Liao et al, 2015).…”
Section: The Regulatory Cascades Of Antibiotic Production In Streptommentioning
confidence: 99%